2002
DOI: 10.1148/radiol.2223010413
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus: Diagnostic Application of Magnetization Transfer Ratio Histograms in Patients with Neuropsychiatric Symptoms—Initial Results

Abstract: With MDA, MTR histograms of brain tissue may provide diagnostic information for individual patients in the clinical context of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
2
19
2
Order By: Relevance
“…In patients with neuro-systemic lupus erythematosus, MTR changes have also been found in the NAWM [105][106][107][108] and have been correlated with the severity of cognitive and neurological impairment, 109 as well as with the activity of the disease. 107 Marked GM-MTR decrease has also been shown in patients with neuro-systemic lupus erythematosus.…”
Section: Cns Vasculitismentioning
confidence: 99%
“…In patients with neuro-systemic lupus erythematosus, MTR changes have also been found in the NAWM [105][106][107][108] and have been correlated with the severity of cognitive and neurological impairment, 109 as well as with the activity of the disease. 107 Marked GM-MTR decrease has also been shown in patients with neuro-systemic lupus erythematosus.…”
Section: Cns Vasculitismentioning
confidence: 99%
“…Dehmeshki and co-workers (Dehmeshki et al, 2002) developed an alternative way of analyzing and globally characterizing MTR histograms by using multivariate discriminant analysis (MDA) and correctly assigned patients with MS to clinical subgroups. The same group proceed to a study in SLE patients in order to explore the diagnostic potential of MDA for assigning patients with SLE to different subgroups of patients with on the basis of MTR histograms (Dehmeshki et al, 2002). MTI was performed to 9 patients with active NPSLE, 10 patients with chronic NPSLE, 10 patients with SLE and no history of NPSLE (non-NPSLE), 10 patients with inactive MS, and 10 healthy control subjects.…”
Section: Magnetization Transfer Imaging (Mti)mentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) may often resemble MS on conventional imaging, although one group (Rovaris et al, 2000b) has shown some success in discriminating between MS and SLE on the basis of MTR histogram metrics. Other workers (Bosma et al, 2000;Dehmeshki et al, 2002c) found that MTR histogram metrics could distinguish between subtypes of neuropsychiatric SLE and that discriminatory power can be improved with multivariate discriminate analysis.…”
Section: Other Diseases Studied With Histogramsmentioning
confidence: 99%